Bangladesh : 2008 Article IV Consultation; Staff Report; Staff Supplement; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bangladesh. (IMF Staff Country Reports; Country Report, 2008)
Bangladesh's 2008 Article IV Consultation reports that growth picked up strongly from a slow start to the year with rebounds in agriculture and garment exports playing a leading role. Strong growth of remittances and increased external assistance helped support the balance of payments in the face of rising import costs. An impressive increase in government revenues, bringing state-owned enterprise losses onto the budget, and the substantial increase in administered prices have been significant achievements.